Maqashid Syariah Menurut Al-Juwayni - Bayu Suhairi, Mhd. Arbi; Tanjung, Dhiauddin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The main purpose of this research is to find out the thoughts of Imam Al- Juwayni in implementing the concept of Maqashid Al-syari “ah in everyday life and integrating maqashid shari ”ah in Islamic religious colleges in general, especially in Islamic religious colleges. This type of research is a literature study or literature study, which contains theories that are relevant to research problems. Data collection techniques using theoretical aspects and aspects of practical benefits. The conclusion of the research is about the correlation of maqasid shari'ah with the method of determining the law in instigating Islamic law.